Path Analysis of Family Communication, Decision-Making, and Caregiver Burden on Family Caregivers’ Quality of Life: The Mediating Role of Self-Efficacy - Setyoadi, Setyoadi; Ismail, Dina Dewi Sartika Lestari; Hayati, Yati Sri; Efendi, Ferry; Haryanto, Joni (Nurse Media Journal of Nursing, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) presents a chronic health challenge that extends beyond the patients, significantly affecting family members who assume caregiving responsibilities. Family caregivers often experience emotional, physical, and psychological burdens, particularly in low-resource settings. However, the interplay between family communication, decision-making, caregiver burden, and self-efficacy, and how these factors jointly influence caregiver quality of life, remains insufficiently explored, particularly in culturally specific and resource-limited settings.Purpose: This study aimed to examine the structural relationships among family communication, shared decision-making, caregiver burden, self-efficacy, and their influence on the quality of life of family caregivers of individuals with T2DM.Methods: A cross-sectional study was conducted involving 327 family caregivers recruited from 16 primary health centers using cluster random sampling. Data were collected using validated instruments to measure family communication, decision-making, caregiver burden, self-efficacy, and quality of life. Structural Equation Modeling (SEM) was used to analyze both direct and indirect relationships among the variables.Results: The findings revealed that family communication (β = 0.35) and decision-making (β = 0.42) had significant positive effects on self-efficacy, whereas caregiver burden (β = -0.33) had a significant negative effect. Self-efficacy, in turn, significantly improved caregivers’ quality of life (β = 0.51). Furthermore, self-efficacy mediated the indirect effects of family communication, decision-making, and caregiver burden on quality of life. The model explained 49% of the variance in self-efficacy and 64% of the variance in caregiver quality of life.Conclusion: Self-efficacy plays a central role in enhancing caregiver well-being and quality of life. Interventions that promote open family communication, shared decision-making, and burden reduction are essential. Nursing implications include the need for culturally sensitive, family-centered nursing interventions to enhance caregiver self-efficacy through communication training, psychosocial support, and empowerment in decision-making. Nurses should be equipped to assess caregiver burden and